ANALISIS DETERMINAN MINAT PENGGUNAAN TELEMEDICINE PADA MAHASISWA FAKULTAS ILMU KESEHATAN UPN "VETERAN" JAKARTA - Sarah Rania Annisa (2024)
Telemedicine provides services by facilitating medical consultations, diagnoses, and treatments without the need for face-to-face interaction. This has the potential to improve and simplify public access to healthcare services. This research was conducted to analyze the factors related to the intention in using telemedicine among students of the Faculty of Health Sciences at UPN "Veteran" Jakarta. The study utilized a quantitative cross-sectional study design. The analysis of relationships on performance expectations, facilitating conditions, effort expectations, social influence, price values, e-Health literacy, privacy issues, and trust was conducted using the Chi Square test. The research results indicate a significant relationship between performance expectation variables (P= 0.002), facilitating conditions (P= 0.006), social influence (P= 0.001), and e-Health literacy (P= 0.002). Meanwhile, effort expectations, price value, privacy issues, and trust were found have no significant relationship. Based on the logistic regression test results, e-Health literacy is the most dominant variable influencing the intention of using telemedicine (P= 0.006) with an Odds Ratio of 49.742 (95% CI 3.173─779.863). The conclusion drawn from this research is that performance expectations, facilitating conditions, social influence, and e-Health literacy have a significant relationship with the intention of using telemedicine, with e-Health literacy being the most dominant variable.